Islamic Religious Education Learning Management In Pringsewu - Josantori, Josantori (Journal of Advanced Islamic Educational Management, 2024)
At SMP Negeri 2 SukoharjoPringsewu, the teaching of Islamic religious education follows an Islamic-based education system. The class hours in the morning are dedicated to Islamic religious education, where Islamic educational theories are incorporated, covering lessons on the Qur'an, hadith, moral creed, and fiqh. This research adopts a descriptive qualitative approach. Data collection is done through interviews, observation, and documentation. The data analysis involves data reduction, followed by presenting it in a descriptive form and verifying it to draw conclusions. The study aims to analyze, identify, and describe the planning, implementation, and evaluation of Islamic religious education at SMP Negeri 2 SukoharjoPringsewu. The findings of this study indicate the following: The planning of Islamic religious education learning at SMP Negeri 2 SukoharjoPringsewu tends to follow a technological concept, emphasizing techniques that foster cognitive behavior and constructive theories to address teaching problems, particularly concerning 'ámaliyah' learning competencies. The teacher employs scientific lecture methods to read, describe, and design Islamic values, using lesson planning theory to encourage students to explore literature related to da'wah methods. The implementation of Islamic religious education learning at SMP Negeri 2 SukoharjoPringsewu adopts the ROPES model, comprising review, overview, presentation, exercise, and summary. The evaluation of Islamic religious education learning at SMP Negeri 2 SukoharjoPringsewu involves assessing the learning tools using observation and interview data.